PENGARUH PENCUCIAN MENGGUNAKAN JERUK NIPIS TERHADAP KUALITAS SARANG BURUNG WALET - Yulianti, Irma; Sukainah, Andi; Caronge, Muhammad Wiharto (Jurnal Pendidikan Teknologi Pertanian, 2019)
This research aims to determine of the effect of swallow nest-washing by lime to its quality. This research is experiment research using completely randomized design (CRD) with washing concentration of water and limes are 2%, 4%, and 6%. Observed parameters are nitrite, ammonia, total plate count, Escherichia coli, and Salmonella sp. The results show the best treatment of swallow nest-washing is obtained from lime-washing 6% with nitrite of 0.046 ppm, ammonia of 0.048 ppm, and total plate count of 2.39 Log cfu/g, also E. coli and Salmonella sp are negative